Sexually acquired acute hepatitis C infection diagnosed during pregnancy: a case report of successful postpartum treatment - Preetha Nandi; Aley G. Kalapila; Martina L. Badell; Anandi N. Sheth (Elsevier, 2018)
Background: Infection with the hepatitis C virus (HCV) during pregnancy has emerged as an increasingly recognized and prevalent condition among women of reproductive age in the United States. While screening recommendations exist for pregnant women at high risk of HCV infection, pregnant women with HCV are often under-screened, not diagnosed, or do not receive adequate follow-up, thereby increasing the risk of suboptimal maternal and infant outcomes (including in future pregnancies). Case: A pregnant woman living with HIV presented with intrahepatic cholestasis of pregnancy. She had tested negative for HCV earlier in pregnancy as part of routine screening recommended for women living with HIV. She was found to have sexually acquired a new HCV infection from her partner during pregnancy. She successfully completed treatment postpartum. Conclusion: With the rise in HCV infection among pregnant patients, physicians should be diligent in assessing pregnant women and their partners for HCV risk factors, testing for HCV when risk is identified, and arranging follow-up testing and treatment for HCV-positive mothers and their infants. Keywords: HCV, HCV in pregnancy, co-infection, HCV screening, high-risk obstetrics, HIV